2022
DOI: 10.1039/d2dt03255d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric acid concentration for nitration of fused [1,2,5]oxadiazolo[3,4-d]pyrimidine-5,7-diamine

Abstract: Nitration reactions are very often used for the selective synthesis of novel, high performing nitramine-based materials. Now nitration reactions of the fused 5,7-diamino pyrimidine derivative 1, under different nitric acid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Although successive progress has been made on the direct connection of furoxan with the five-membered ring, a structure connected with the bicyclic structure has not been reported so far. Recent studies have shown that the introduction of a fused-ring skeleton can effectively increase the enthalpy of formation, thereby further enhancing detonation performance [25][26][27]. In order to simultaneously accomplish the oxygen balance boost, the oxa- [5,5]bicyclic ring is a preeminent candidate structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although successive progress has been made on the direct connection of furoxan with the five-membered ring, a structure connected with the bicyclic structure has not been reported so far. Recent studies have shown that the introduction of a fused-ring skeleton can effectively increase the enthalpy of formation, thereby further enhancing detonation performance [25][26][27]. In order to simultaneously accomplish the oxygen balance boost, the oxa- [5,5]bicyclic ring is a preeminent candidate structure.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the oxa- [5,5]bicyclic ring energetic compounds of furoxan were obtained through the ring-closing reaction of amino-protected chloroxime furoxan and 2chloro-4-nitro-1H-imidazole under alkaline conditions, followed by deprotection of the amino group. The oxidation products and azo products were also successfully prepared, and all compounds were deeply characterized using 1 H, 13 C, 14 N NMR spectroscopy, high- Recent studies have shown that the introduction of a fused-ring skeleton can effectively increase the enthalpy of formation, thereby further enhancing detonation performance [25][26][27]. In order to simultaneously accomplish the oxygen balance boost, the oxa- [5,5]bicyclic ring is a preeminent candidate structure.…”
Section: Introductionmentioning
confidence: 99%